Proposed Model of Sharia Bank Share Ownership through Waqf Funds - Siregar, Saparuddin; Ridwan , M.; Siregar, Hilyati Inayah; Rahmadana, Muhammad Fitri (Journal of Ecohumanism, 2024)
This paper presents a feasibility model for Sharia Bank share ownership through Waqf funds as an alternative source of capital. It begins by addressing the problem of insufficient capital stock for Islamic banks in Indonesia. The exploration includes banking regulations by the Indonesian Financial Services Authority, Sharia Waqf laws and regulations by the Indonesian Waqf Board, and literature in the field of Waqf, as well as secondary sources such as books, journal articles, and online resources, particularly those related to Waqf regulation. Conclusions are drawn by analyzing several themes, which are further validated through in-depth interviews and Focus Group Discussions with experts. This paper introduces Cash Waqf as a potential source of paid-in capital for Islamic banks, particularly in Indonesia.